Creating Meaningful Science Learning: A Differentiated Instruction Approach to Understanding Spring Energy Concepts in Elementary School - Harlinda Syofyan; Laeli Zohandiah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to analyze the implementation of differentiated science learning on spring energy material in elementary schools. This qualitative research with a case study design involved one class IV consisting of 28 students (14 males, 14 females) with a distribution of learning styles: 8 visual students (28.57%), 7 auditory students (25%), and 9 kinesthetic students (32.14%). Data collection was carried out through learning observations, in-depth interviews with 6 students representing the three learning styles, and analysis of learning documentation. The results showed that the level of learning implementation reached 90% conformity with the developed teaching module. The achievement of learning outcomes showed consistency, with an average score of 85 for each learning style group. Interviews revealed positive student responses to learning that was fun and made it easier to understand the material. The success of the implementation was supported by thorough teacher preparation and the availability of diverse learning media. However, there were challenges in terms of limited preparation time and the complexity of classroom management. This study proves the effectiveness of differentiated science learning in accommodating the diversity of elementary school students' learning styles.